IMPLEMENTASI FSM (FINITE STATE MACHINE) PADA GAME MALIK LOOKS FOR THE HOLY BOOK - Adam Abiyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi Nasional Malang, 2023)
The development of the gaming industry has required developers tocreating a more immersive gaming experience. In this context,the use of Finite State Machines (FSM) has become a popular and effective solution inmanaging the storyline and more structured character development. This articleaims to review the basic concepts of FSM and describe its implementationin the game